Protein-Protein Interaction Assays - Ansari, Mahmood-ur-Rahman (IntechOpen, 2018)
The chapters in this book are written by a team of well-reputed international researchers. The objective is to provide advanced and updated information related to protein-protein interactions. I hope the methods, resources and approaches described here will enhance the available knowledge of the reader significantly.